Food safety : researching the hazard in hazardous foods - Almanza, Barbara A.; Ghiselli, Richard; Khan, Mahmood A. (Oakville, Ontario : Apple Academic Press, 2014)
The book provides a thorough review of current food safety and sanitation information with practical applications of current research findings included. The book surveys and examines the prevailing research and applications and reviews specific operational issues such as power or water emergencies. It also covers food safety and sanitation in various environments, such as restaurants, schools, and fairs and festivals. It is multidisciplinary in that it comprises culinary, hospitality, microbiology, and operations analysis. Topics include: Importance of food safety in restaurants; History of food safety regulation in restaurants; Microbiological issues; What happens during a restaurant food safety inspection; Legislative process, regulatory trends, and associations; Legal issues for food safety; Differences in the food safety perception of consumers, regulatory officials, and employees; What restaurants should do during power or water emergencies; Front of the house sanitation and consumers' perceptions of food safety; Social media and food safety risk communication; Food safety in farmers' markets; Food safety at fairs and festivals.
1. Importance of food safety in restaurants / Richard Ghiselli -- 2. History of food safety and food safety regulation in the United States / Barbara Almanza and Jeff Fisher -- 3. Microorganisms in foods: a historical perspective / Jay Neal -- 4. What happens during food establishment inspections in the United States / Barbara Almanza -- 5. Legislative process, regulatory trends, and associations / Kevin R. Roberts, Brenda H. Halbrook and Jeannie Sneed -- 6. Food safety and the law: understanding the real-life liability risks / Dennis Stearns -- 7. Hand washing / Jim Mann -- 8. Training and certification: in researching the hazard in hazardous foods / Robin B. DiPietro -- 9. Differences in the food safety perceptions of consumers, employees, and regulatory officials / Ameet Tyrewala -- 10. What restaurants should do during power or water emergencies / Ameet Tyrewala -- 11. Front of the house sanitation and consumers' perceptions of sanitation / Haeik Park -- 12. Social media and food safety risk communication / Soobin Seo -- 13. Food safety in temporary foodservice establishments / Carl Behnke -- 14. Hotel guest room cleaning: a systematic approach / Sheryl F. Kline, Barbara A. Almanza and Jack'Jay' Neal -- 15. Food safety in schools / Kevin Sauer and Jeannie Sneed -- 16. Food safety at fairs and festivals / Huey Chern Boo and Wei Leong Chan --17. Foodservice and seniors in meals on wheels programs and congregate meat sites: a service with challenges / Lionel Thomas -- 18. Dealing with disasters / Sandra Sydor -- 19. Food Defense concepts / Sarah Slette, Mary Stiker and A. Scott Gillian -- 20. Global issues / Jin-Kyung Choi and Jeff Fisher -- 21. Travel health concerns / Kelly Way.
Includes bibliographical references and index.
Keywords: Food adulteration and inspection; Food -- Safety measures; Restaurants -- Sanitation; Food -- Microbiology